Analysis of dose to the macula, optic disc, and lens in relation to vision toxicities – A retrospective study using COMS eye plaques. (September 2022) - Oare, Courtney; Sun, Susan; Dusenbery, Kathryn; Reynolds, Margaret; Koozekanani, Dara; Gerbi, Bruce; Ferreira, Clara
Highlights: Ocular dose limits are necessary to evaluate a novel intraocular shielding method. Retrospective study reviewed dosimetry and toxicity data for eye plaque patients. Doses>52 Gy to the macula and 42 Gy to the optic disc should be avoided. Further work is needed to reduce high doses and improve patients' quality of life. Abstract: Purpose: The aim of this study was to relate common toxicity endpoints with dose to the macula, optic disc, and lens for uveal melanoma patients treated with Iodine-125 Collaborative Ocular Melanoma Study (COMS) eye plaque brachytherapy. Methods: A cohort of 52 patients treated at a single institution between 2005 and 2019 were retrospectively reviewed. Demographics, dosimetry, and clinical outcomes were recorded. Univariate, relative risk, and Kaplan-Meier analyses were performed to relate dose to toxicity endpoints including retinopathy, vision decline, and cataracts. Results: By the end of follow up (Median = 3.6 years, Range = 0.4 – 13.5 years), 65 % of eyes sustained radiation retinopathy, 40 % demonstrated moderate vision decline (>5 Snellen lines lost), and 56 % developed cataracts. Significant (p < 0.05) risk estimates exist for retinopathy and VA decline for doses >52 Gy to the macula and >42 Gy to the optic disc. Moreover, dose to the lens > 16 Gy showed a significant risk for cataract formation. Kaplan-Meier analysis demonstrated significantly different incidence of radiation retinopathy for > 52 Gy to the macula and > 42 Gy to the optic disc. In addition, the Kaplan-Meier analysis showed significantly different incidence of cataract formation for patients with lens dose > 16 Gy. Conclusions: Dose-effect relationships exist for the macula and optic disc with respect to the loss of visual acuity and the development of retinopathy. To better preserve vision after treatment, further research is needed to reduce macula, optic disc, and lens doses while maintaining tumor control.